PERMAINAN TRADISIONAL BANDARAN MODIFIKASI TERHADAP KEMAMPUAN MENGENAL BILANGAN PADA ANAK TUNAGRAHITA RINGAN - Firman, Mochammad (Jurnal Pendidikan Khusus, 2016)
Abstract This research of the influence of Modification Bandaran traditional game toward recognizing numbers ability to mild mentally retardation children in SLB Harmoni Sidoarjo was formed the background by cognitive ability of mild mentally retardation children that was recognizing numbers i.e. mentioning and writing number 1 – 10 so that the researcher gave fun activity which could facilitate the mentally retardation children to learn understanding numbers through modification Bandaran traditional game. The mathematics learning activity of recognizing numbers by using modification Bandaran traditional game had never been applied yet in SLB Harmoni Sidoarjo. This research purpose was to prove whether there was influence of modification Bandaran traditional game toward recognizing numbers to mild mentally retardation children in SLB Harmoni Sidoarjo or not. The samples in this research were 7 children whose recognizing numbers ability still needed to be developed. This research used quantitative approach and the data collection used test and observation. The data collection technique used statistic non parametric with wilcoxon match pairs test. The research result indicated that there was enhancement of recognizing numbers ability in SLB Harmoni Sidoarjo with the early observation result to mentally retardation was 37,5 to be 71 in the last observation to mentally retardation. The research result also indicated that T counted = 0 was smaller than T table = 0,02 with 5% signification level. If T counted = 0 < T table = 0,02 so it could be concluded that there was influence of modification Bandaran traditional game toward recognizing numbers ability to mentally retardation children in SLB Harmoni Sidoarjo.   Keywords: modification Bandaran,  recognizing numbers